A Block Classification Method with Monitor and Restriction in NAND Flash memory (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we propose a block classification with monitor and restriction (BCMR) method to isolate and reduce the interference of blocks in garbage collection and wear leveling. The proposed method monitors the endurance variation of blocks during garbage collection and detects hot blocks by making a restriction condition based on this information. This method induces block classification by its update frequency for garbage collection and wear leveling, resulting in a prolonged lifespan for NAND flash memory systems. The performance evaluation results show that the BCMR method prolonged the life of NAND flash memory systems by 3.95% and reduced the standard deviation per block by 7.4%, on average.